Ratiometric upconversion nanothermometry with dual emission at the same wavelength decoded via a time-resolved technique - Xiaochen Qiu (Nature Portfolio, 2020)
Traditional ratiometric temperature monitoring is challenging due to the variation in tissue absorption and scattering of different wavelengths. Here, the authors show improved accuracy by using emission at the same wavelength, but different luminescent lifetimes decoded by a time-resolved technique.